Case Report: Multiple Cavernous Pericardial Lymphangioma (Pericardial Lymphangiomatosis) in a Captive Peregrine Falcon (Falco peregrinus brookei) - Espinosa, José; Ferreras, M. Carmen; García, David; Vallejo, Raquel; Pérez, Valentín (Frontiers in Veterinary Science, 2021)
A 12-year-old female peregrine falcon (Falco peregrinus brookei) from a private raptor breeding facility that presented a good body condition, died suddenly without showing previous symptoms. At necropsy, in the coelomic cavity, multiple cystic structures demarcated by a thin transparent wall and filled with a serous content were observed. They were firmly adhered to the cranial part of the epicardium and adjacent tissues and occupied the entire thoracic area of the coelomic cavity. Microscopically, emerging simultaneously from several areas the epicardium, multiple irregular channels and cystic spaces, lined by a single endothelial cell layer and separated by fibrovascular septa containing smooth muscle tissue, were observed. Immunohistochemical examination revealed that the neoplastic endothelial cells positively immunolabelled for the pan-endothelial marker factor VIII-related antigen but immunostained negative for cytokeratins (PCK26) while strong positivity for sarcomeric α-smooth muscle actin (α-SMA) was detected in the cystic walls. Based on the morphological and immunohistochemical findings, lesions were determined as consistent with a multiple cavernous pericardial lymphangioma, or pericardial lymphangiomatosis, a rare vascular neoplasm. The animal also showed a diffuse chronic perihepatitis, a necrotic area in the liver and foci of cartilaginous metaplasia and calcification in the aorta and vena cava. Literature review, particularly on the epidemiology of lymphangioma, demonstrated the rarity of this tumor in the different animal species and in this location, particularly in birds, being the first report of this type of tumor in a peregrine falcon.